The theology of Paul the Apostle - Dunn, James D. G., 1939-2020. (Grand Rapids, MI William B Eerdmans Publishing Company, 1998)
Using Paul's letter to the Romans as the foundation for his monumental study of Paul's theology, James D.G. Dunn describes Paul's teaching on God, sin, humankind, Christology, salvation, the church, and the nature of the Christian life.
In this major work, James D. G. Dunn brings together more than two decades of vigorous and creative work on interpreting the letters of Paul into an integrated, full-scale study of Paul s thought. Using Paul s letter to the Romans as the foundation for constructing a fuller exposition of Paul s whole theology, Dunn s thematic treatment clearly describes Paul s teaching on such topics as God, humankind, sin, christology, salvation, the church, and the Christian life. In the process Dunn engages in a concise way what other important scholars have said regarding each area of inquiry. The Theology of Paul the Apostle represents a major contribution to the ongoing discussion regarding what Paul s theology is and what its continuing relevance is to the study and practice of religion and theology. -- ‡c From publisher's description.
Chapter 1. Prologue -- Chapter 2. God and Humankind -- Chapter 3. Humankind Under Indictment -- Chapter 4. The Gospel of Jesus Christ -- Chapter 5. The Beginning of Salvation -- Chapter 6. The Process of Salvation -- Chapter 7. The Church -- Chapter 8. How Should Believers Live? -- Chapter 9. Epilogue.
Includes bibliographical references (pages xix-xxviii) and indexes.
Keywords: Paul, -- the Apostle, Saint; Bible. -- Theology